Adults Fail to Learn a Type of Linguistic Pattern that is Readily Learned by Infants. Issue 4 (2nd October 2019) - Gerken, LouAnn; Quam, Carolyn; Goffman, Lisa
ABSTRACT: Beginning with the classic work of Shepard, Hovland, & Jenkins (1961), Type II visual patterns (e.g., exemplars are large white squares OR small black triangles) have held a special place in investigations of human learning. Recent research on Type II linguistic patterns has shown that they are relatively frequent across languages and more frequent than Type IV family resemblance patterns (e.g., exemplars have 2 out of 3 defining features). Research has also shown that human infants are adept at learning Type II patterns from very few exemplars, but adult learning appears to be more mixed. Because no study had directly compared adults and infants, Experiment 1 tested both groups on the same input and test stimuli. Adults at best showed weak learning of one of two Type II patterns, but infants showed robust learning of both patterns. Experiment 2 contrasted adults' ability to learn a Type II pattern with a Type IV pattern. Adults only showed learning of the latter, replicating previous research with different stimuli and testing procedures. Thus, adults are unable to learn a frequent linguistic pattern, one readily learned by infants. Implications for possible language learning differences between infants and adults are discussed.